PRODUCTION FORMAT OF BTU TLAK PROGRAM ON YOUTUBE - Buranadechachai, Sukanya; Nualnetr, Prapas; Na nakorn, Rattiporn (Journal of MCU Nakhondhat, 2026)
The BTU TALK program is Public Relations Media’s BangkokThonburi University. This research aims to 1) study the BTU TALK program production process, 2) study Audience Satisfaction 3) present the program format on YouTube. research is a qualitative research method was used, in-depth focus group interviews. A set of interview questions was used to gather opinions from the sample groups, with audio recordings and data recordings kept in notebooks. The same method was used for all three groups: Group 1 consisted of 7 television program experts; Groups 2 and 3 comprised 5 third-year Communication Arts students from Bangkok Thonburi University with knowledge of television program production to determine the program structure, and 15 students to study viewer satisfaction after watching the program. The research findings showed that: 1) The program is produced using a block-style presentation structure with three segments: Break 1 presents university news, Break 2 features interviews with renowned personnel, and Break 3 showcases Communication Arts student activities. 2) Audience Satisfaction was found to be positive in seven aspects of the program format: program structure, program sequence, guest appearances, graphics, entertainment (comedy clips), media utilization, and the YouTube platform. 3) Three-break appropriate on YouTube. Interview break should be concise with subtitles. Break 3 should be added, in-depth Report. YouTube is a suitable platform for distribution and should be linked with other online media to increase reach. New episodes should be released on Saturdays or Sundays from 11:00 AM to 1:00 PM. More than one host is recommended, each presenting a different segment. The interview segment can be presented in two ways: 1) With a main host in the studio and a field host, or 2) With a Talking Head style interview format. Include prize-winning questions and BTU Game Cards to engage students and create a unique program identity.